Distribution Strategies Analysis Using AHP and TOPSIS: A Distribution Company Case’s Study in Special Region of Yogyakarta, Indonesia - Teny Sylvia; Noveliska Br Sembiring; Nadia Ulfiyati (Journal of Science and Applicative Technology, 2021)
The selection of distribution strategy is important for the company in order for the product to be delivered to the customer in time and according to the required quality and quantity. This research aims to analyze and determine the company's distribution strategy using the AHP and TOPSIS methods. The results of the calculations with AHP indicate that the distributor reliability is seen from the history and experience (0268), effective fund management (0159), and the financial structure of the distributor (0147) are three criteria with the weight of interest highest. The geographical strategy is a strategy that has the highest value so it is recommended to be the main strategy of the company in distributing products to customers.